Current status and prospects for the transformation of teaching methods in the study of medical and biological disciplines in higher education - Tymchyk, Olesia; Nevedomska, Yevheniia (Educological discourse, 2026)
This article analyzes the effectiveness of implementing modern educational technologies in the teaching of medical and biological disciplines (MBD) at institutions of higher education. Based on a student survey and statistical analysis using the Cheddock scale and the authors’ heat maps, the intensity of innovative teaching methods’ use was assessed. It has been empirically proven that the blended learning and “flipped classroom” models dominate (67,0% of responses; high intensity according to Cheddock). At the same time, a significant gap was identified between the theoretical potential and the practical implementation of high-tech solutions: gamification and VR/AR technologies have the lowest level of integration due to resource constraints and the lack of standardized methodologies. The methodologies of “microlearning,” “peer-to-peer,” and “project-based learning” are fragmented in nature (r = 0,3–0,4), serving only a supplementary, stimulating function. A high rate of independent development of interactive tasks by students was recorded (64,9%, r = 0,65), which is a positive sign, since it is precisely independence and interactivity that shift the student from the position of an observer to that of an active participant. This result indicates the readiness of future specialists for active learning, despite a lack of skills in creating complex didactic materials and video content. Recommendations are proposed for the systematic integration of research-based learning into a blended learning framework, the implementation of mobile augmented reality (AR), and the development of methodological standards for the use of artificial intelligence while upholding academic integrity. The transformation of MBE education must occur at the intersection of technological accessibility, scientific methodology, and the practical relevance of educational content to the demands of modern education.